2023
DOI: 10.3389/fpls.2023.1126884
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of TPS genes in Gossypium and their characteristics in response to flooding stress

Abstract: Terpene synthases (TPS) is a key enzyme in the synthesis of plant terpenoids. Studies on TPSs have not been reported in Gossypium barbadense and Gossypium arboreum. 260 TPSs were identified in Gossypium, including 71 in Gossypium hirsutum, 75 in Gossypium. barbadense, 60 in Gossypium. arboreum, and 54 in Gossypium raimondii. We systematically analyzed the TPS gene family of Gossypium from three aspects: gene structure, evolutionary process and gene function. (1) Gene structure: Based on the protein structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…To reveal whether replication and loss have occurred, we performed a colinear analysis of all TPS genes in diploid G. arboreum and G. raimondii and tetraploid G. hirsutum ( Figure 3 ). When PF01397 and PF03936 were used as indexes to scan the whole genome for identification of TPS family genes, it was found that there were 75 TPS genes in G. arboreum , 60 in G. raimondii , and only 91 in G. hirsutum without any filtration ( Huang et al., 2018 ; Cui et al., 2023 ). Collinearity analysis showed that 22 sequences showed collinearity between G. arboreum and G. hirsutum , and 20 sequences showed collinearity between G. raimondii and G. hirsutum .…”
Section: Resultsmentioning
confidence: 99%
“…To reveal whether replication and loss have occurred, we performed a colinear analysis of all TPS genes in diploid G. arboreum and G. raimondii and tetraploid G. hirsutum ( Figure 3 ). When PF01397 and PF03936 were used as indexes to scan the whole genome for identification of TPS family genes, it was found that there were 75 TPS genes in G. arboreum , 60 in G. raimondii , and only 91 in G. hirsutum without any filtration ( Huang et al., 2018 ; Cui et al., 2023 ). Collinearity analysis showed that 22 sequences showed collinearity between G. arboreum and G. hirsutum , and 20 sequences showed collinearity between G. raimondii and G. hirsutum .…”
Section: Resultsmentioning
confidence: 99%
“…We found this pattern concurs with the overall molecular phylogeny of Solanaceae, where the genus Nicotiana is at a more basal level than Capsicum and Solanum on the phylogenetic tree 22 . It is observed that tandem duplication played an important role in the occurrence of tabacumexclusive clades 27 . The tandem duplication accounts for the formation of gene clusters of the same gene family and confers new phenotypic traits 28 .…”
Section: Discussionmentioning
confidence: 99%